Exploring the future model of organisations: The changing role of HR and organisational leaders - Chauhan, Sanjeev; Sharma, Avnish; Panicker, Aneesya (International Journal of Psychosocial Rehabilitation, 2020)
Digital transformation in the business world has already been triggered the gaps in leadership capabilities and skills. Leaders need to manage this change which is washing over every organization. HR leaders will need to move ahead of traditional top-down change management and go for more agile and responsive mechanisms. Innovations in technology are proposing new challenges before the organizations in the form of new business models. Recent trends in technologies, the way data is analyzed and people are networking with each other globally is creating a significant impact on the style of communication and work management. As organizations continue to transform, the leadership roles will also continue to change and orientation of having leadership pipeline with potential successors for specific positions or roles can no longer sustain with the demands of uncertain, rapidly changing times. The biggest challenge before the leaders and HR professionals is the management of multigenerational and diversified workforce, leading to the advent of a more complex and varied category of roles, responsibilities and leadership styles. Altogether these changes are going to affect the talent management & development practices of business organizations. Here a billion-dollar question comes with this changing scenario that how the management of organizations will attract, retain and motivate their diversified people as a key asset? And how is the role of leaders and management of HR going to change as a result? This paper mulls over the expected series of scenarios for the management of multigenerational diversified people. The purpose is to provide a lens in the form of three ‘Business Model of Work’ through which organizations can examine how they might operate in the future and understanding the role of human resource managers and organisational leaders in this changing context.